Glycemic index, glycemic load, dietary carbohydrate, and dietary fiber intake and risk of liver and biliary tract cancers in Western Europeans. - Fedirko, V; Lukanova, A; Bamia, C; Trichopolou, A; Trepo, E; Nöthlings, U; Schlesinger, S; Aleksandrova, K; Boffetta, P; Tjønneland, A; Johnsen, N; Overvad, K; et al. (2013)
BACKGROUND: The type and quantity of dietary carbohydrate as quantified by glycemic index (GI) and glycemic load (GL), and dietary fiber may influence the risk of liver and biliary tract cancers, but convincing evidence is lacking. PATIENTS AND METHODS: The association between dietary GI/GL and carbohydrate intake with hepatocellular carcinoma (HCC; N = 191), intrahepatic bile duct (IBD; N = 66), and biliary tract (N = 236) cancer risk was investigated in 477 206 participants of the European Prospective Investigation into Cancer and Nutrition cohort. Dietary intake was assessed by country-specific, validated dietary questionnaires. Hazard ratios and 95% confidence intervals were estimated from proportional hazard models. HBV/HCV status was measured in a nested case-control subset. RESULTS: Higher dietary GI, GL, or increased intake of total carbohydrate was not associated with liver or biliary tract cancer risk. For HCC, divergent risk estimates were observed for total sugar = 1.43 (1.17-1.74) per 50 g/day, total starch = 0.70 (0.55-0.90) per 50 g/day, and total dietary fiber = 0.70 (0.52-0.93) per 10 g/day. The findings for dietary fiber were confirmed among HBV/HCV-free participants [0.48 (0.23-1.01)]. Similar associations were observed for IBD [dietary fiber = 0.59 (0.37-0.99) per 10 g/day], but not biliary tract cancer. CONCLUSIONS: Findings suggest that higher consumption of dietary fiber and lower consumption of total sugars are associated with lower HCC risk. In addition, high dietary fiber intake could be associated with lower IBD cancer risk.